Gabapentin in procedure-specific postoperative pain management – preplanned subgroup analyses from a systematic review with meta-analyses and trial sequential analyses - Maria Louise Fabritius; Anja Geisler; Pernille Lykke Petersen; Jørn Wetterslev; Ole Mathiesen; Jørgen Berg Dahl (BMC Anesthesiology, 2017)
Abstract Background It has been argued that postoperative pain treatment should be “procedure-specific”, since different analgesics may have specific effects dependent on the surgical procedure. The aim of the present subgroup analysis was to compare the beneficial and harmful effects of perioperative gabapentin treatment in different surgical procedures. Methods Relevant databases were searched for randomized clinical trials (RCTs) comparing gabapentin versus placebo. Two authors independently screened titles and abstracts, extracted data and assessed risk of bias. The primary outcomes were differences in 24-h morphine consumption, and serious adverse events (SAE) between surgical procedures. These subgroup analyses were predefined in a PRISMA compliant systematic review registered at PROSPERO (ID: CRD42013006538). It was predefined that conclusions should primarily be based on trials classified as overall low risk of bias. Results Seventy-four RCTs with 5645 patients were included, assessing benefit and harm in cholecystectomy, hysterectomy, mastectomy, and arthroplasty surgery, spinal surgery, and thoracic surgery. Only eight of 74 trials were classified as overall low risk of bias limiting our ability to conclude on the estimates in most meta-analyses. The differences between surgical procedures in these trials were not statistically significant when tested for subgroup differences. Fifteen trials with 1377 patients reported a total of 59 SAEs, most of which were observed in the thoracic surgery group. Conclusion Both beneficial and harmful effects in these subgroup analyses were influenced by bias and insufficient data, limiting conclusions. With these limitations, we could not adequately test for differences in beneficial or harmful outcomes between six surgical subgroups undergoing perioperative gabapentin treatment.